99mTc-pertechnetate uptake in parotid acinar cells by the Na+/K+/Cl- co-transport system. - Helman, J (1987)
99mTc-Pertechnetate (99mTcO4-) has widespread clinical use in the diagnosis and evaluation of dysfunctions in many different tissues. However, despite the broad clinical application of this radionuclide, very little is known about the mechanism by which 99mTcO4- enters a cell. We report evidence here that 99mTcO4- shares the Na+/K+/Cl- co-transport system localized to the basolateral membrane of rat parotid acinar cells. 99mTcO4- uptake by these cells was quite rapid (t1/2 approximately 30 s), was completely inhibited by the loop diuretics furosemide and bumetanide, and was markedly dependent on the presence of Na+, K+, and Cl- in the extracellular medium. Relative to uptake measured in the presence of physiological extracellular salt concentrations (Hanks' salts), 99mTcO4- uptake was inhibited 80% by sodium replacement and 50% by potassium replacement. When Cl- was replaced with the physiologically inert anion gluconate a threefold stimulation in 99mTcO4- uptake resulted. These observations provide strong evidence that 99mTcO4- can substitute for Cl- as a substrate for the Na+/K+/Cl- co-transporter and indicate that 99mTcO4- uptake by salivary glands (e.g., as seen with salivary scintiscans), and possibly by a variety of other tissues, reflects the functional activity of this co-transport mechanism.